Energy saving campaign: by the student for the students - Zainuddin, Mohamad Faiz; Mohamad Zaid, Siti Sarah (Centre for Global Open Access Learning, Immersive Technology & Quality Assurance, Universiti Sains Islam Malaysia, 2017)
Social influence through persuasion technology could be key in promoting energy conservation practices among university students who are avid users of social media sites. Although there is a plethora of resources on energy conservation available online, students would feel compelled to view online resources produced by their own circle of friends. Social media sites allow students to publish their works seamlessly and viewed by their peers instantly. Interactive communication on social media sites encourage lecturers’ and students’ participation in the campaign.